SISTEM PENERTIBAN OPERASIONAL ANGKUTAN UMUM DAN BARANG DALAM WILAYAH KOTA BANDA ACEH: Menurut Konsep Milk al-Daulah dan Qanun No. 6 Tahun 2018 Studi Penelitian pada Dishub Banda Aceh - Sapitri, Rahmi; Abdullah, Muslem; bin Adnan , Boihaqi (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2025)
This study examines the operational control system for public and freight transportation in Banda Aceh City using the concept of milk al-daulah and referring to Qanun Nomor 6 of 2018. This study uses an empirical juridical approach with a descriptive qualitative approach that focuses on the implementation of control by the Banda Aceh Transportation Agency. The results show that the milk al-daulah concept strengthens the basis for state ownership and management of transportation facilities, while Qanun No. 6 of 2018 establishes legal regulations that clearly and systematically regulate aspects of transportation operations. Operational control is carried out through routine supervision, inter-agency coordination, and the application of administrative sanctions. However, several challenges remain, such as limited supervision and suboptimal public participation. Operational control is carried out through routine supervision such as checking route permits, vehicle roadworthiness tests, and mandatory entry to terminals, as well as coordination with various agencies, especially the Regional Police Traffic Unit to implement administrative sanctions. This study recommends improving the monitoring system and providing guidance to transportation operators to create orderly, safe, and efficient transportation services in Banda Aceh